2020
DOI: 10.1002/ijgo.13423
|View full text |Cite
|
Sign up to set email alerts
|

The use of alpha‐2‐macroglobulin as a novel treatment for patients with chronic pelvic pain syndrome

Abstract: Synopsis Alpha‐2‐macroglobulin shows potential for use as an adjunctive treatment option for chronic pelvic pain syndrome when injected into Alcock’s canal using a hydrodissection technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Alpha-2 M Activation by Proteases Alpha-2 M is a plasma proteinase inhibitor with inflammatory properties that regulates the distribution and activity of many cytokines [58][59][60][61][62]. Though the exact mechanism is not known, animal models and human studies have demonstrated that proteolytic enzymes, such as trypsin and bromelain, are absorbed as physiologically intact molecules [63][64][65].…”
Section: Pharmacodynamics Of Orally Administered Enzymesmentioning
confidence: 99%
“…Alpha-2 M Activation by Proteases Alpha-2 M is a plasma proteinase inhibitor with inflammatory properties that regulates the distribution and activity of many cytokines [58][59][60][61][62]. Though the exact mechanism is not known, animal models and human studies have demonstrated that proteolytic enzymes, such as trypsin and bromelain, are absorbed as physiologically intact molecules [63][64][65].…”
Section: Pharmacodynamics Of Orally Administered Enzymesmentioning
confidence: 99%
“… 8 With pelvic pain, patients can experience a deep, aching sensation in a discrete location or with a regional distribution. 22 In hypertonic pelvic floor dysfunction, the muscles are short, spastic, and weak with palpable MTrPs. Chronically contracted, weak muscles can lead to a local restriction in blood flow and a change in the environmental pH, which will in turn trigger the inflammatory cascade and perpetuate or cause neurogenic inflammation 85 (Fig.…”
Section: Etiologymentioning
confidence: 99%